Oxidative Stress in Emergency Toxicology - M. V. Belova; K. K. Ilyashenko; Ye. A. Luzhnikov (Общая реаниматология, 2009)
Objective: to comparatively assess the intensity of oxidative stress (OS) in acute poisonings by various toxic chemicals. Subjects and methods. Two hundred and eighty-seven patients with acute poisoning by psychopharmacological agents, ethanol, and cauterants were examined. Results. A correlation was found between the manifestations of OS and the severity of poisoning. The investigators revealed the impacts of exposure to toxic chemicals and complications of the toxicogenic phase of acute poisoning by the above toxicants on the intensity of OS. Conclusion. The intensity of OS in the poisonings under study increases in proportion to the severity of intoxication, toxicant exposure in the body. The presence of hemolysis, upper airway burn, and chronic alcoholism deteriorate OS. Key words: oxidative stress, acute poisonings, chemical burn, chronic alcoholism.